THE EFFECT OF INSTRUCTIONAL APPROACH AND VERBAL REASONING ON STUDENTS’ SCIENTIFIC WRITING ABILITY - Ratu Wardarita (JETL (Journal of Education, Teaching and Learning), 2017)
The objective of this research is to find out the difference between instructional approaches and verbal reasoning on students’ scientific writing ability. It was conducted at  Indonesian Language  Study Program, Faculty of Teacher Training and Education, University of PGRI Palembang. This research employed the experimental method using 2x2 factorial Anova test, with 43 students chosen randomly through multi-stage sampling technique. The results of this research indicate that: (1) the group of students taught with the contextual teaching and learning (CTL) approach has better than taught with the conventional one; (2) the group of high-level verbal reasoning students taught with CTL approach has better than taught with the conventional one; (3) the group of low-level verbal reasoning students taught with the CTL approach has lower than taught with the conventional one; (4) there is an interaction effect between instructional approach and the level of verbal reasoning on students’ scientific writing ability.